2020
DOI: 10.1080/09638288.2020.1773940
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation interventions after traumatic brain injury: a scoping review

Abstract: Purpose: To 1) identify interventional research topics in traumatic brain injury (TBI) rehabilitation, 2) describe potential knowledge gaps, and 3) uncover further needs for interventional TBI rehabilitation research for patients and families.Method: We searched three databases (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) and screened 1552 non-duplicate articles.Titles and abstracts were screened for relevance, yielding 754 articles for full-text review. Of these, 425 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Gaps during RTW and recovery reported by participants in this study are similar to those outlined by other researchers, for instance: (a) better collaboration between employers and healthcare professionals during RTW; (b) access to qualified professional expertise and interdisciplinary care; (c) need for social support and employer support; and (d) better awareness of mental, physical, and cognitive consequences of a TBI [31,32]. Researchers have recommended that post-TBI recovery programs should include more comprehensive considerations for the following groups: older patients; individuals with mild/moderate TBI; and individuals in the acute (0-6 weeks) and sub-acute (7 weeks-3 months) phases of rehabilitation [31]. It has also been suggested that there is a need for further research on RTW and activities of daily living post-TBI, the role of families and social networks, peer support, and continuity of post-concussion care [31].…”
Section: Discussionsupporting
confidence: 86%
“…Gaps during RTW and recovery reported by participants in this study are similar to those outlined by other researchers, for instance: (a) better collaboration between employers and healthcare professionals during RTW; (b) access to qualified professional expertise and interdisciplinary care; (c) need for social support and employer support; and (d) better awareness of mental, physical, and cognitive consequences of a TBI [31,32]. Researchers have recommended that post-TBI recovery programs should include more comprehensive considerations for the following groups: older patients; individuals with mild/moderate TBI; and individuals in the acute (0-6 weeks) and sub-acute (7 weeks-3 months) phases of rehabilitation [31]. It has also been suggested that there is a need for further research on RTW and activities of daily living post-TBI, the role of families and social networks, peer support, and continuity of post-concussion care [31].…”
Section: Discussionsupporting
confidence: 86%
“…They can result in long rehabilitation processes involving various health care and social services, and, according to the injured persons themselves, several unmet needs (Andelic et al, 2014). However, rehabilitation interventions seldom address employment (Sveen et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It's been reported that the incidence of STBI ranks rst in the all types of trauma, accounting for 9% to 21% of trauma in all parts of the body, and the mortality is as high as 50% [2,3]. In recent years, with the improvement of trauma treatment and the development of intensive care medicine, the mortality of STBI has declined, but the quality of life and daily living ability of surviving TBI patients have declined signi cantly [4]. Therefore, it is necessary to carry out long-term nursing care and health education for such patients to promote their quality of life.…”
Section: Introductionmentioning
confidence: 99%